KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA METEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS V SDIT AL-MUMTAZ PONTIANAK - Syahruda Syahruda; Bistari Bistari; Siti Halidjah (Universitas Tanjungpura, 2022)
AbstractThis research to describe student ability to solve math story problems in terms of thelearning independence class V student at SDIT Al-Mumtaz Pontianak. Research methodused is descriptive method. Subjects in this research are students of class V C. Subjectstaking is done by giving a learning independence questionnaire to students of class V Cwhich then from the results of the questionnaire selected 6 subjects purposive based onthe category of learning independence. Sources of data in this study consisted of theresults of a learning independence questionnaire, test results of story questions andresults of interviews. The results of this research indicate that students with high levelof learning independence are able to solve problems well and fulfill all problem solvingindicators. Students with moderate level of learning independence are able to solveproblems quite well and fulfill all problem solving indicators, but they are still notthorough in doing calculations. Students with low levels of learning independence notenough to solve the problems, students do not understand the question so wrong indetermining how to answer questions, students are also not able to carry out the correctcalculation procedure in counting fractions.Keywords: Ability to Solve Math Story Problems, Learning Independece